Development of a Human Factors Methods Blog for an Audience of Game Developers. (September 2016) - Trowbridge, Francis A.; Pybus, Lawton; Mudrick, Nicholas; Taub, Michelle
We, as human factors practitioners and researchers, often must describe what we study, how we do it, and why it matters. As a part of those efforts, we developed a blog introducing human factors methods and their applications for an audience of game developers. Each method is discussed and illustrated using examples applied to games. We also describe our goals for the blog's style and structure, and ideas for further refinement.